Technology Adoption Model on Higher Education Learning Environments - Garaika Garaika; Rahajeng Arundati; Dyah Sugandini; Yuni Istanto; Rava Fernanda Purnama (AIBPM Publisher, 2021)
This study examines technology adoption in higher education university learning environments in the Special Region of Yogyakarta. The object of this research is the e-learning system innovation in universities in the Yogyakarta region. This study focuses on the individual internal characteristics that influence e-learning adoption. This research's internal factors are user motivation, perceived Ease of use, trust, and technology readiness. This survey is a type of survey in university students, analyzing the adoption of e-learning technology using student respondents. While the method used is quantitative. This survey uses a questionnaire as a tool to collect data. The number of samples in this study is 150 students. Analyze the data using a structural model with Partial Least Square. This research indicates that the e-learning adoption model in the university environment, influenced by trust, motivation, perceived ease of use, and perceived technology readiness, is acceptable. The results of this study indicate that all proposed hypotheses can be accepted.